White-Collar Crime and Stock Return: Empirical Study from Announcement Effect - Wei, Samuel Siew Liew; Puah, Chin-Hong (Universiti Malaysia Sarawak (UNIMAS), 2011)
White-collar crime continues to hit the headlines across Malaysia and it remains a serious issue influencing organizations globally. A share price event study is thus conducted on a group of public listed companies in Malaysia to examine the announcement effect of white-collar crime. The period of the study is from 1996 to 2010, covering both the Asian Financial Crisis in 1997/98 and the sub-prime mortgage crisis in 2008/09. Results indicate the existence of significant negative abnormal share price reaction on 10 trading days subsequent to the day of announcement. It means that the stock market in Malaysia is not efficient. However, it implies that the market possesses the power to discipline unethical companies as the shareholders drive down their value by disposing their stocks following the announcement.